Simulação em laminador piloto da influência da lubrificação durante o processo de deformação a quente na microestrutura e textura do aço inoxidável ferrítico AISI 430 - Henrique de Castro Rodrigues (2008)
This work deals simulation and characterization of the influence lubrication during hot deformation in AISI 430 ferritic stainless steel in a Steckel mill process. A characterization of industrial process AISI 430 thermo mechanical cycle simulation from slab reheating until finish annealed coil has been presented. A microstructure and texture characterization has been provided for pilot hot strip rolled and microstructure, texture, mechanical and hoping tests for pilot cold strip rolled after finish annealed process. The quantification of presents phases (recrystallised and non-recrystallised ferritic fraction and martensite) isnt appropriated for Tz concept (modify temperature byZenner-Hollomon equation), that used temperatures near the Fe-C-Cr diagram biphasic region range, where thin carbides was indexed which martensite in EBSD analysis. Lubrication during hot deformation process has large influence in reduced shearing textures and fiber homogeneity through hot band samples thickness, showing lesses mechanical efforts in the hot and cold rolling process: decreasing in hot and cold rolling loads, with possibility to reduce one cold rolling pass and to improve productivity gain, and a better ridging level, but, present a bad point: poor drawability caused for reduced in the fibers e relation in the cold rolling samples.